Ethical study of the virtue of justice in the verses of the rulings "With the approach of moral analysis of the verses of retribution" - Seyedahmad Hashemialiabadi; Mohammad Javad Hassanzadeh (اخلاق وحیانی)
The present article examines the relationship between the two areas of ethics and jurisprudence in the context of the interaction of verses related to retribution based on the interpretive method of verse to verse and interpretive sources to examine the moral examples of the virtue of justice "with the approach of educational analysis of verses" in retribution Paid. The main purpose of this study is the significant effect of the teachings of Islamic ethics in jurisprudential verses and specifically in matters of retribution. Ethical support of jurisprudential instructions based on the verses and the gradual way of expressing the verses of retribution, the two axes manifested in this study are considered. Accordingly, after inferring the moral teachings of justice in the verses of Al-Qisas, justice can be proposed in three areas: "equality in quantity", "forgiveness after proving a crime" and "being bound by example in social matters and specific members". The data processing method of the present article is library and its content review method is descriptive-analytical.